Keratocystoma of minor salivary gland of the palate - Gourav Ahuja; Kamaldeep Kaur Aulakh; Eish Sethi; Varun Nagpal; Harkanwal Kaur (Wolters Kluwer Medknow Publications, 2016)
The authors analyzed the clinical, histopathological, and immunohistochemical findings of a slowly growing palatal gland tumor in a 34-year-old female. The cut surface of the excised mass showed multilocular cystic spaces with grayish brown solid areas. Histological findings demonstrated a benign tumor with multicystic spaces and focal solid epithelial cells lined by benign squamous epithelial cells. The overlying epithelium was parakeratinized and without a granular layer. The cystic spaces were filled with keratin material. On immunohistochemistry examination, the tumor cells were found positive for HMWCK, focally for CK7, CK19 and p63 and Mib-1 labeling was approximately 1%. There was no evidence of recurrence after 8 months of resection. The data from this case and previously published studies suggest that keratocystoma of both major and minor salivary glands is a benign neoplasm and that surgical resection is apparently a sufficient treatment modality.